Repeated Sand Fly Bites of Infected BALB/c Mice Enhance the Development of Leishmania Lesions - Vojtkova, Barbora; Frynta, Daniel; Spitzova, Tatiana; Lestinova, Tereza; Votypka, Jan; Volf, Petr; Sadlova, Jovana (Frontiers in Tropical Diseases, 2021)
Sand fly saliva has considerable immunomodulatory effects on Leishmania infections in mammalian hosts. Studies on several Leishmania – sand fly - host combinations have demonstrated that co-inoculation with Leishmania parasites enhances pathogenicity, while pre-exposure of hosts to sand fly bites provides significant protection against infection. However, the third scenario, the effect of sand fly saliva on parasite development in hosts infected before exposure to sand flies, remains an understudied aspect of Leishmania–host–vector interaction. Here we studied the effect of exposure of L. major-infected BALB/c mice to repeated sand fly bites. Mice infected intradermally with sand fly-derived Leishmania were repeatedly bitten by Phlebotomus duboscqi females every two weeks. The lesion development was recorded weekly for ten weeks post-infection and parasite load and distribution in various organs were tested post mortem using qPCR. Repeated sand fly bites significantly enhanced the development of cutaneous lesions; they developed faster and reached larger size than in unexposed mice. Multiple sand fly bites also increased parasites load in inoculated ears. On the other hand, the distribution of parasites in mice body and their infectiousness to vectors did not differ significantly between groups. Our study provides the first evidence that multiple and repeated exposures of infected BALB/c mice to sand fly bites significantly enhance the progress of local skin infection caused by Leishmania major and increase tissue parasite load, but do not affect the visceralization of parasites. This finding appeals to adequate protection of infected humans from sand fly bites, not only to prevent transmission but also to prevent enlarged lesions.